Safe motherhood in crisis; threats, opportunities, and needs: a qualitative study - Sedigheh Moghassemi; Elham Adib Moghaddam; Sahar Arab (BMC, 2024)
Abstract Background The coronavirus disease (COVID)-19 pandemic has affected many aspects of life, including pregnancy, childbirth, and safe motherhood so that pregnancy and childbirth take place in completely novel and unusual conditions for people. Therefore, we aimed to determine the opportunities, threats, and needs of pregnant women during a crisis. Methods The present qualitative study was conducted among women who had a history of pregnancy and childbirth during the COVID-19 pandemic period in 2022. The data were collected by conducting face-to-face, semi-structured and in-depth interviews with 20 purposefully selected participants. Interviews continued until data saturation was attained. Data were analyzed through conventional qualitative content analysis based on the Graneheim and Lundman approach. Results The data were categorized under three main themes: 1("Opportunities for safe motherhood in crisis"(2 Sub‑themes), 2) "Threats to safe motherhood in crisis"(2 Sub‑themes), and 3) "Needs for safe motherhood in crisis" (3 Sub‑themes). Conclusions Crisis is not always a threat. By developing an awareness of the opportunities, threats, and needs that safe motherhood faced during the COVID-19 crisis, policy makers can identify the existing gaps affecting the health of mothers and take the necessary measures to improve their conditions, experiences, and health in further crises.